Creep deformation and rupture behaviour of thermal aged P92 steel. (2nd January 2016) - Sakthivel, T.; Panneer Selvi, S.; Parameswaran, P.; Laha, K.
Abstract : Creep deformation and rupture behaviour of thermal aged P92 steel have been investigated over a stress range of 110–130 MPa at 923 K. Laves phase was observed in the thermal aged steel. Laves phase predominantly coarsens towards the intra-lath region assisted by substructure within the lath region. The stress dependence of minimum creep rate followed Norton's power law of creep with comparable apparent stress exponent value in the thermal aged, and normalised and tempered steels. The creep rate and creep rupture lives of both the steels were relatively comparable under lower stress level. The steel obeyed Monkman–Grant and modified Monkman–Grant ductility relationships. Enhanced precipitation of Laves phase has been observed at the necked region in both the conditions of the steel, which experienced higher plastic flow. Thermal aging of P92 steel has not significantly influenced the creep strength under longer creep duration.